2011
DOI: 10.4161/pri.5.4.17748
|View full text |Cite
|
Sign up to set email alerts
|

The yeast prions [PSI+] and [URE3] are molecular degenerative diseases

Abstract: The yeast prions [URE3] and [PSI] are not found in wild strains, suggesting they are not an advantage. Prion-forming ability is not conserved, even within Saccharomyces, suggesting it is a disease. Prion domains have non-prion functions, explaining some conservation of sequence. However, in spite of the sequence being constrained in evolution by these non-prion functions, the prion domains vary more rapidly than the remainder of the molecule, and these changes produce a transmission barrier, suggesting that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
(42 reference statements)
0
21
0
Order By: Relevance
“…Thus, some authors have suggested that prions are adaptive bet-hedging devices or evolutionary capacitors that empower survival in intermittently stressful and fluctuating environments (Halfmann et al, 2010; Halfmann and Lindquist, 2010; Lancaster et al, 2010; Masel and Bergman, 2003; Masel and Griswold, 2009; Shorter and Lindquist, 2005; Shorter, 2010; Tuite and Serio, 2010). Conversely, others contend that yeast prions are molecular degenerative diseases more akin to mammalian neurodegenerative disorders (Wickner et al, 2007; Wickner et al, 2011). However, the fact that yeast prions can confer strong selective advantages under defined conditions separates them from simple degenerative disorders that are invariably deleterious.…”
Section: Yeast Prions: Good or Evil Or Both?mentioning
confidence: 99%
“…Thus, some authors have suggested that prions are adaptive bet-hedging devices or evolutionary capacitors that empower survival in intermittently stressful and fluctuating environments (Halfmann et al, 2010; Halfmann and Lindquist, 2010; Lancaster et al, 2010; Masel and Bergman, 2003; Masel and Griswold, 2009; Shorter and Lindquist, 2005; Shorter, 2010; Tuite and Serio, 2010). Conversely, others contend that yeast prions are molecular degenerative diseases more akin to mammalian neurodegenerative disorders (Wickner et al, 2007; Wickner et al, 2011). However, the fact that yeast prions can confer strong selective advantages under defined conditions separates them from simple degenerative disorders that are invariably deleterious.…”
Section: Yeast Prions: Good or Evil Or Both?mentioning
confidence: 99%
“…1 In the budding yeast Saccharomyces cerevisiae several different proteins can propagate alternative conformations via a prion-like mechanism and thus serve as epigenetic switches that produce heritable phenotypes. 2 Although it has been suggested that yeast prions represent disease states, [3][4][5][6] the evolution of prion domains in a variety of yeast proteins and the occurrence of prions in wild yeast populations raise the possibility that such a mechanism may also have important biological roles. 7,8 A well-studied example is the [PSI C ] prion, which is a selfpropagating amyloid form of the translation termination factor Sup35.…”
Section: Introductionmentioning
confidence: 99%
“…Most yeast prions are intracellular amyloids inherited in a nonMendelian fashion (via cytoplasm) and containing QN-rich prion domains that resemble mammalian proteins associated with polyglutamine disorders such as Huntington's disease. Some yeast prions are pathogenic to the yeast "host" (41,68), thus establishing yeast as a model for studying the pathogenic amyloids. Other yeast prions are widespread in nature, pointing to potentially positive biological effects (23).…”
mentioning
confidence: 99%